Dynamics of skin microvascular blood flow in 4–6-year-old children in association with pre- and postnatal black carbon and particulate air pollution exposure. (December 2021) - Witters, Katrien; Dockx, Yinthe; Op't Roodt, Jos; Lefebvre, Wouter; Vanpoucke, Charlotte; Plusquin, Michelle; Vangronsveld, Jaco; Janssen, Bram G.; Nawrot, Tim S.
Highlights: Cardiovascular health in adulthood can find its roots during prenatal development. Air pollution exposure during prenatal life can affect the microvasculature. Heat-induced skin hyperemia in children as dynamic marker of the microvasculature. Skin perfusion in children can be assessed using laser Doppler probes. Inverse association between skin perfusion and prenatal air pollution exposure. Abstract: Background: A growing body of evidence indicates that cardiovascular health in adulthood, particularly that of the microcirculation, could find its roots during prenatal development. In this study, we investigated the association between pre- and postnatal air pollution exposure on heat-induced skin hyperemia as a dynamic marker of the microvasculature. Methods: In 139 children between the ages of 4 and 6 who are followed longitudinally within the ENVIR ON AGE birth cohort, we measured skin perfusion by Laser Doppler probes using the Periflux6000. Residential black carbon (BC), particulate (PM10 and PM2.5 ) air pollution, and nitrogen dioxide (NO2 ) levels were modelled for each participant's home address using a high-resolution spatiotemporal model for multiple time windows. We assessed the association between skin hyperemia and pre- and postnatal air pollution using multiple regression models while adjusting for relevant covariates. Results: Residential BC exposure during the whole pregnancy averaged (IQR) 1.42 (1.22–1.58) µg/m 3, PM10 18.88 (16.64 – 21.13) µg/m 3, PM2.5 13.67 (11.5 – 15.56) µg/m 3 and NO2 18.39 (15.52 – 20.31) µg/m 3 . An IQR increment in BC exposure during the third trimester of pregnancy was associated with an 11.5 % (95% CI: −20.1 to −1.9; p = 0.020) lower skin hyperemia. Similar effect estimates were retrieved for PM10, PM2.5 and NO2 (respectively 13.9 % [95% CI: −21.9 to −3.0; p = 0.003], 17.0 % [95% CI: −26.7 to −6.1; p = 0.004] and 12.7% [95 % CI: –22.2 to −1.9; p = 0.023] lower skin hyperemia). In multipollutant models, PM2.5 showed the strongest inverse association with skin hyperemia. Postnatal exposure to BC, PM10, PM2.5 or NO2, was not associated with skin hyperemia at the age of 4 to 6, and did not alter the previous reported prenatal associations when taken into account. Conclusion: Our findings support that BC, particulate air pollution, and NO2 exposure, even at low concentrations, during prenatal life, can have long-lasting consequences for the microvasculature. This proposes a role of prenatal air pollution exposures over and beyond postnatal exposure in the microvascular alterations which were persistent into childhood.